Development of the external and internal shame scale: Japanese version - Hiramatsu, Yoichi (2021)
Objective: Shame contains external and internal aspects. However, a Japanese language scale for simultaneously assessing both aspects of shame has not been developed to date. This study aimed to standardize the Japanese version of the External and Internal Shame Scale (EISS-J). An online survey was conducted among university students (N=203) at six universities in Japan (Study 1). A retest questionnaire was sent to the participants by email three weeks after the first survey (Study 2). Study 1 examined the internal consistency, factor structure, and criterion-related validity of the EISS-J, while Study 2 examined its test-retest reliability. Moreover, an additional study was conducted to examine the criterion-related validity of the scale. Results: Study 1 demonstrated the high internal consistency of the EISS-J. Moreover, confirmatory factor analysis indicated a two-factor model: external and internal shame. However, exploratory factor analysis indicated a three-factor structure. Study 2 confirmed the test-retest reliability of the scale. Furthermore, both studies indicated correlations between the EISS-J and fear of compassion, anger, humiliation, depression, anxiety, and stress. In addition, the study established the criterion-related validity of the scale. These results confirmed adequate reliability and validity of the EISS-J.